A Monoclonal Antibody-Based Qunatitative Enzyme Immunoassay for the Determination of Plasma Fibrinogen Concentartions - Hoegee-de Nobel, E; Voskuilen, M; Briët, E; Brommer, E J P; Nieuwenhuizen, W (Thrombosis and Haemostasis, 1988)
The most commonly used fibrinogen assays in the clinic are clotting rate assays, e.g. the Clauss method. Such functional assays may be disturbed by e.g. heparin, anticoagulant fibrinogen degradation products (FgDP) and in the case of a dysfi-brinogenemia. Immunological methods would not suffer from these interferences. However, immunological assays for fibrinogen, which do not measure FgDPs, do not exist.To set up such an enzyme immunoassay (EIA) we developed two monoclonal antibodies. The first monoclonal antibody (G8) has its epitope in the carboxyl-terminal 150 amino acid stretches of the fibrinogen Aa-chains. G8 is used to coat the wells of microtitration plates, and is the capture antibody in this EIA. The second antibody (Y18) has been described by us previously (Blood 1985; 66: 503). It is directed against fibrinopeptide A, covalently bound to the ±-chains i.e. against the amino-terminal stretches of the A±-chains. Y18 is conjugated with horse-radish peroxidase, and used as tagging antibody.The EIA does not react with, and is not interfered by FgDP such as purified fragments X and Y, up to a concentration of 800 μg/ml. An FgDP mixture such as generated by Streptokinase treatment of plasma does not respond. Fibrin degradation products (whole blood lysate) up to 800 μg/ml do not interfere nor do heparin, EDTA or oxalate. The time-to-result of the EIA is only 45 minutes. Some patient plasmas yielded dose-response curves which are not parallel with the calibration curve of the EIA. An explanation for this phenomenon could not be given. Our fibrinogen EIA may be especially suitable to monitor patients with conditions which favour proteolytic damage to fibrinogen such as thrombolytic therapies.
Keywords: Enzyme immunoassay; Fibrinogen; Monoclonal antibodies